2017
DOI: 10.1515/hukin-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Sprint, Jumping and Strength Abilities, and 800 M Performance in Male Athletes of National and International Levels

Abstract: This study analysed the relationships between sprinting, jumping and strength abilities, with regard to 800 m running performance. Fourteen athletes of national and international levels in 800 m (personal best: 1:43-1:58 min:ss) completed sprint tests (20 m and 200 m), a countermovement jump, jump squat and full squat test as well as an 800 m race. Significant relationships (p < 0.01) were observed between 800 m performance and sprint tests: 20 m (r = 0.72) and 200 m (r = 0.84). Analysing the 200 m run, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
4
19
1
Order By: Relevance
“…Regarding the sprint variables, a significant improvement of performance in 200 m throughout the season can be observed. This result shows that the distance of 200 m is probably more related to the performance in 800 m than other shorter distances as 20 m. Similarly, significant correlations between 800 and 300 m running times (Deason et al, 1991 ), and between 800 and 200 m have been found (Bachero-Mena et al, 2017 ). Therefore, strength and sprint-related variables seem to be relevant in the 800 m performance.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Regarding the sprint variables, a significant improvement of performance in 200 m throughout the season can be observed. This result shows that the distance of 200 m is probably more related to the performance in 800 m than other shorter distances as 20 m. Similarly, significant correlations between 800 and 300 m running times (Deason et al, 1991 ), and between 800 and 200 m have been found (Bachero-Mena et al, 2017 ). Therefore, strength and sprint-related variables seem to be relevant in the 800 m performance.…”
Section: Discussionmentioning
confidence: 67%
“…However, these events are shorter than the 800 m. In accordance with our findings, Hudgins et al ( 2013 ) observed significant correlations between jumping ability and 800 m race time in competitive runners. Likewise, significant correlations between CMJ, JS, and SQ with performance in 800 m in high-level athletes have been found (Bachero-Mena et al, 2017 ). Contrary to our study, Balsalobre-Fernández et al ( 2015 ) did not find significant improvements in strength parameters during an athletics season in middle and long-distance athletes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At the very least, the addition of MSS allows for enhanced potential analysis (see Figures 1A,B ), and is a technically and methodologically easy addition to most study designs. However, very rarely, are any maximal speed/power and/or biomechanics based metrics reported or considered (despite considerable evidence showing them to be important performance determinants of MSS Weyand et al, 2000 , 2010 ; Morin et al, 2011 ; Rabita et al, 2015 ; Nagahara et al, 2019 ) as well as determinants of middle-distance race performance (Nummela et al, 1996 ; Bachero-Mena et al, 2017 ; Sandford et al, 2019a ).…”
Section: Middle-distance Running—the Event Group With Largest Diversimentioning
confidence: 99%
“…In sport and everyday activities, one of the most important attributes of skeletal muscle is the ability to generate power, a product of strength and speed of movement [14]. Research has shown a strong relationship between strength, 20 m sprinting, and jumping performance in athletes and field sports athletes [15,16]. Another study [17] reported that a strong correlation exists between half-squat maximum strength, 30 m sprint performance, and jump height in soccer players.…”
Section: Introductionmentioning
confidence: 99%